Colour’s Profile of Longissimus Dorsi Beef at Different Kluwek Addition Levels and Marinating Times - Wicaksono, A. D.; Nur, A.; Irwan, I. (Hasanuddin Journal of Animal Science (HAJAS), 2025)
Beef is a common food in everyday life. The longissimus dorsi muscle, known as rib eye, is one of the primary cuts of beef due to its tenderness and marbling, making it highly valued for culinary purposes. Meanwhile, kluwek (Pangium edule), a plant widely found in Southeast Asia and known locally as kepayang, is traditionally used as an antioxidant, preservative, and natural colouring agent in food preparation.  This study aims to analyze the colour profile of Longissimus dorsi beef by evaluating the effects of different levels of kluwek addition and marination times. The experiment was designed using a 5x4 factorial pattern with three replications. The first factor was the kluwek level (L1 = 0%, L2 = 2%, L3 = 4%, L4 = 6%), and the second factor was the marination time (W0 = 0 minutes, W1 = 30 minutes, W2 = 60 minutes, W3 = 90 minutes, W4 = 120 minutes).  Results indicated that the lightness (L*) of the beef was significantly affected (P<0.05) by the addition of 6% kluwek, with an interaction observed between kluwek levels and marination times. Redness (a*) was not significantly influenced (P>0.05) by any of the treatments, while yellowness (b*) was significantly reduced (P<0.05) with the addition of 6% kluwek.  In conclusion, adding 6% kluwek effectively alters the lightness (L*) and yellowness (b*) of the beef, while redness (a*) remains stable. This study highlights the potential of kluwek, a local ingredient, to enhance the visual properties of beef during marination. Keywords: Kluwek, Longissimus dorsi, Marinating time